2024
DOI: 10.1021/acs.energyfuels.3c05051
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and Thermodynamic Evidence of the Paal–Knorr and Debus–Radziszewski Reactions Underlying Formation of Pyrroles and Imidazoles in Hydrothermal Liquefaction of Glucose–Glycine Mixtures

Hanifrahmawan Sudibyo,
Budhijanto Budhijanto,
Daniela V. Cabrera
et al.

Abstract: We evaluated Paal−Knorr and Debus−Radziszewski reactions as the mechanisms underlying formation of pyrroles and imidazoles, respectively, in hydrothermal liquefaction (HTL) via semicontinuous HTL experiments on a glucose−glycine mixture. We developed cheminformatic-based HTL reaction pathways for a range of feedstock pH (2−12), reaction temperatures (280−370 °C), and reaction times (2−60 min). The developed pathways were validated using transient concentration of the reacting compounds and assessed using rever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
(120 reference statements)
0
1
0
Order By: Relevance
“…While Long et al observed how two-stage HTL can weaken the Maillard reaction pathway, having a low-pH played an important role for further inhibition of such a reaction leading to reduction in N content (Table ) and reduced % area of N-heterocyclics and amides/amines (Table ) in the bio-oils. Some N-compounds were still detected under acidic conditions due to alternate reaction mechanisms including formation of pyrroles and imidazoles from Paal-Knorr and Debus-Radziszewski reactions involving dicarbonyls, primary amine, and ammonia . Phenols detected in bio-oils can also be attributed to lignin degradation .…”
Section: Resultsmentioning
confidence: 99%
“…While Long et al observed how two-stage HTL can weaken the Maillard reaction pathway, having a low-pH played an important role for further inhibition of such a reaction leading to reduction in N content (Table ) and reduced % area of N-heterocyclics and amides/amines (Table ) in the bio-oils. Some N-compounds were still detected under acidic conditions due to alternate reaction mechanisms including formation of pyrroles and imidazoles from Paal-Knorr and Debus-Radziszewski reactions involving dicarbonyls, primary amine, and ammonia . Phenols detected in bio-oils can also be attributed to lignin degradation .…”
Section: Resultsmentioning
confidence: 99%